Gender Stereotypes and Bias in Nursing: A Qualitative Study in Tanzania - Racheal Mukoya Masibo; Golden M. Masika; Stephen M. Kibusi (Nursing Reports)
(1) The question addressed in this study is what kinds of stereotypes and biases of gender in nursing exist in Tanzania. This study aimed to investigate gender stereotypes and bias among healthcare providers and non-healthcare providers. (2) Methods: Qualitative descriptive design and data were collected from the Dar es Salaam region of Tanzania through a Focus Group Discussion approach. The qualitative content analysis was used to obtain themes the following themes. (3) Results: Three themes and eighteen subthemes emerged from this study. The first theme is role distribution based on nurse gender, its impact, and mitigating approaches for biased role distribution; the second theme is the different ways of addressing challenges in gender in nursing diversity; and the third theme is gender in nursing biases at the training institutions. (4) Conclusions: The bias and stereotypes about gender in nursing still exist in clinical areas and training institutions. Exercising professionalism in both settings remains a vital aspect of reducing bias. Moreover, role distribution should not be dominated by social roles of men and women in the community but rather should be based on competence and individual abilities.